A Study on Subsidence Problem in Kusma Area, Parbat District (Journal of Nepal Geological Society, 1993)
The Kusma terrace is about 250 m high above the Kaligandaki River bed. It is composed of highly cemented conglomerate of unsorted subangular to rounded pebble to boulder sized rock fragments of metasandstone, limestone, quartzite, gneiss and phyllite. Owing to calcareous cementing matrix conglomerate is maturely karstified with formation of prominent features of tower karst, pinnacles, solution chimneys and fissures. Solution channels are filled up by slope wash deposit of recent age. The subsurface now through these channels scours the unconsolidated slope wash deposit and ultimately cause land subsidence and sink holes.